Prediksi Tingkat Kesehatan Lingkungan Masyarakat Dalam Program Sustainable Development Goals Menggunakan Algoritma Naive Bayes - Kusrini Kusrini; Sudarmawan Sudarmawan; Zulkipli Zulkipli (Infotek: Jurnal Informatika dan Teknologi, 2023)
Indications of a decrease in the level of public awareness about protecting the environment have a direct effect on the urgent need for integrated environmental planning and management, so that the impact affects other aspects, such as the physical and socio-economic environment. The fact is that environmental damage is closely related to poverty and economic growth. In maintaining community environmental health and implementing the Sustainable Development Goals Program in East Lombok Regency, West Nusa Tenggara. Hamzanwadi University is working with the East Lombok Regency government to conduct sampling of the community with a total data of 4624 residents in ten sub-districts in the East Lombok Regency area. The purpose of this study is to help predict the level of public environmental health in the East Lombok region, the data will be classified and then processed using the Naïve Bayes algorithm with the multinomial naïve Bayes method. The results of testing the naïve Bayes algorithm after splitting the data five times, the best results were obtained, with the dataset divided by 20% testing data and 80% training data, an prediction value of 93.28% was obtained. The population environment in ten sub-districts in East Lombok Regency was classified as healthy